Efektivitas latihan buerger allen exercise dan senam kaki diabetes terhadap sirkulasi perifer dan gejala neuropati pada pasien diabetes melitus - Santika, I Made; Peristiowati, Yuli; Wahyuningsih, Atik Setiawan; Prasetyo, Joko; Nurdina, Nurdina; Yulianti, Desak Made (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Diabetes mellitus (DM) is a chronic metabolic disease frequently accompanied by complications such as peripheral circulatory disorders and neuropathy, which contribute to decreased lower-extremity function. This condition is still often found in DM patients at Toto Kabila Regional Hospital, highlighting the need for effective non-pharmacological interventions. Purpose: To analyze the effectiveness of buerger allen exercise and diabetic foot exercise in improving peripheral circulation and neuropathic symptoms among patients with diabetes mellitus. Method: A quasi-experimental two-group pretest–posttest design involving 60 patients who were randomly assigned into two intervention groups. Both exercises were administered for four weeks. Data were collected using standardized operational procedures for each exercise along with instruments assessing peripheral circulation and neuropathic symptoms. The Wilcoxon test was used to analyze within-group effects, while the Mann–Whitney test was applied to compare differences between groups. Results: Both interventions significantly improved peripheral circulation and reduced neuropathic symptoms (p = 0.000). Between-group analysis showed that the Buerger Allen Exercise produced greater improvement in peripheral circulation, particularly in the left extremity (p = 0.019), and demonstrated a more substantial reduction in neuropathic symptoms compared to diabetic foot exercise (p = 0.000). Conclusion: Both Buerger Allen Exercise and diabetic foot exercise are effective in enhancing peripheral circulation and reducing neuropathic symptoms in patients with diabetes mellitus. However, Buerger Allen Exercise shows superior effectiveness and may be recommended as a primary non-pharmacological intervention to improve vascular and sensory function in diabetic patients. Keywords: Buerger Allen Exercise; Diabetes Mellitus; Diabetic Foot Exercise; Diabetic Neuropathy; Peripheral Circulation. Pendahuluan: Diabetes melitus (DM) merupakan penyakit kronis yang sering disertai komplikasi berupa gangguan sirkulasi perifer dan neuropati, yang berdampak pada penurunan fungsi ekstremitas bawah. Kondisi ini masih banyak dijumpai pada pasien DM di RSUD Toto Kabila, sehingga diperlukan intervensi non-farmakologis yang efektif. Tujuan: Untuk menganalisis efektivitas Buerger Allen Exercise dan senam kaki diabetes terhadap sirkulasi perifer dan gejala neuropati pada pasien DM. Metode: Desain quasi-experimental two group pretest–posttest dengan total sampel 60 pasien yang dibagi menjadi dua kelompok intervensi. Latihan diberikan selama empat minggu, dan pengukuran dilakukan menggunakan SOP latihan serta instrumen penilaian sirkulasi perifer dan gejala neuropati. Analisis data menggunakan uji Wilcoxon untuk mengetahui pengaruh intervensi dan uji Mann-Whitney untuk melihat perbedaan antar kelompok. Hasil: Peningkatan signifikan pada sirkulasi perifer dan perbaikan gejala neuropati pada kedua kelompok (p = 0.000). Perbandingan antar kelompok menunjukkan bahwa Buerger Allen Exercise memberikan peningkatan sirkulasi perifer yang lebih tinggi, khususnya pada ekstremitas kiri (p = 0.019), serta perbaikan gejala neuropati yang lebih besar dibandingkan senam kaki diabetes (p = 0.000). Simpulan: Buerger allen exercise dan senam kaki diabetes sama-sama efektif meningkatkan sirkulasi perifer dan memperbaiki gejala neuropati, namun buerger allen exercise menunjukkan efektivitas yang lebih unggul. Latihan ini dapat direkomendasikan sebagai intervensi non-farmakologis dalam upaya meningkatkan fungsi vaskular dan sensorik pada pasien diabetes melitus. Kata Kunci: Buerger Allen Exercise; Diabetes Melitus; Neuropati Diabetik; Senam Kaki Diabetes; Sirkulasi Perifer.